Conceptualizing a Resilient Supply Chain for Single-fuel Biomass Power Plant. Issue 1 (June 2018) - Bhaskar, Kalyan; Jain, Nikunj Kumar
India is taking several steps to decarbonize electricity as part of the climate change mitigation efforts. One of those steps has been to promote electricity generation from biomass. Past research has focused on risks related to technology, cost, financing, policy, and supply chain in case of biomass power, but there have been limited studies on risks arising due to climate change. Climate change can have major implications for the supply chain of biomass power plants by affecting the underground water availability and land productivity and thereby affecting the availability of biomass for power plants. The effect could be more acute for single-fuel biomass power plants rather than for multi-fuel biomass power plants. Using data from an 8 megawatt (MW) biomass power plant and by developing a conceptual model, this article models risks arising due to climate change and assesses their likely impact on single-fuel biomass power plants. Two key insights emerge from the analysis: (a) A supply chain that is not sustainable and resilient to climate change impacts poses a major risk to the profits of a biomass power plant; and (b) Single-fuel biomass power plants may need to change their businesses and sourcing strategies by either turning into multi-fuel biomass power plant or by increasing the catchment area of their sourcing.